PHARMACEUTICAL STUDY OF HEMGARBHA POTTALI RASA - Ved Bhushan, Sharma; Parul, Sharma; G.K., Saxena; Usha, Sharma (International Journal of Ayurveda and Pharma Research, 2015)
The Pottali rasayana is a unique preparation in Ayurveda as it is very compact in structure and quick acting due to its high potency. Hemgarbha pottali rasa is a medicine which is known as emergency medicine of Ras shastra because of its efficacy and its quick effect in condition like Sannipataj awastha. It is prepared with the combination of Shudha parada, Shudha gandhaka, Shudha tamra bhasma and Shudha swarna. Preparation method of this Hemgarbh pottali ras is unique in the way that it is prepared in molten sulphur which increases its efficacy many folds. Inspite of availability of vast theoretical description in Ayurvedic texts regarding Pottali rasayana, very less research work is carried out on Hemgarbh pottali rasa, so it is mostly out of practice in Ayurvedic community. Hemgarbh pottali rasa is a very potent medicine which should be made popular by Ayurvedic practitioners. In the present article various methods of preparation of Hemgarbh pottali rasa has been described and most common method of preparation which is molten sulphur method is discussed in detail.